Non-fatal Bihemispheric Penetrating Brain Injury from a Crossbow Arrow with Good Clinical Outcome: Case Report - Januário, José Gonçalo de Oliveira Machado Saraiva; Almeida, Gonçalo Abreu Mesquita Borges de; Calado, Carlos José Rios Godinho; Monteiro, Joaquim António Toscano Ferreira (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2021)
Crossbow injuries to the head have seldom been reported in the literature, and they represent a unique type of penetrating brain injury (PBI) in which a low-velocity arrow results in an intracranial fragment larger than most high-velocity projectiles, usually with a lethal outcome. We present the case of a 34-year-old man who attempted suicide with a self-inflicted cranial injury from a crossbow arrow, with a right parietal point of entry and a palpable subcutaneous tip in the left parietal region. The emergency team reported a Glasgow coma scale (GCS) score of 15, and the patient was brought sedated and intubated. Computed tomography (CT) imaging scans showed that the arrow crossed both parietal lobes, with mild subarachnoid hemorrhage and small cerebral contusions adjacent to its intracranial path. Careful retrograde removal of the penetrating arrow was performed in the CT suite, followed by an immediate CT scan, which excluded procedure-related complications. The patient woke up easily and was discharged 3 days later with mild left hand apraxia and no other neurologic deficits. To the best of our knowledge, there are no similar case reports describing both good clinical outcome and rapid discharge after a bihemispheric PBI. Individualizing the management of each patient is therefore crucial to achieve the best possible outcome as PBI cases still represent a major challenge to practicing neurosurgeons worldwide.
Keywords: Craniocerebral Trauma; penetrating brain injury; foreign bodies; posttraumatic subarachnoid hemorrhage